Development of sustainable plant protection programs through multi-actor Co-innovation: An 8-year case study in Swedish apple production. (10th October 2019) - Swiergiel, Weronika; Manduric, Sanja; Rämert, Birgitta; Porcel, Mario; Tasin, Marco
Abstract: This article assesses the multi-actor co-innovation research that was carried out between 2010 and 2018 by researchers and apple production actors. The aim was to develop sustainable integrated pest management methods that, with the help of an agroecological whole system approach, would be both desirable and feasible to implement in practice. Whilst a novel pest management strategy based on semiochemicals arrived at and was rapidly adopted by growers, the enhancement of biological control through functional diversity required long-term learning. This is explained by substantial differences in the perception of the economic risk and the necessary knowledge behind the adoption of each method. The knowledge gap due to the reduced number of extension advisors and the conflict between the cost incurred when implementing low-impact pest control methods and reduced profitability of apple crops were pointed out as major contradictions by the actors. We suggest that strengthened regional agroecological infrastructure support along with the expansion of public advisory service personnel would reduce the farmer economic risk and share the responsibility for a safer environment and healthier food. Similarly, relevant authorities should be provided with resources to allow for safety assessments of candidate low-risk plant protection products at the regional scale. As a conclusion, we recognised that in our region sustainable agroecosystem management through feasible and desirable plant protection strategies could not be developed solely by focussing on the efficiency of the tools because the cost-effectiveness and thus the implementation of such tools depended greatly on the simultaneous co-innovation of the socio-technical system. Local stakeholders need to harmonise their vision and standpoints to engender long term socially and environmentally sound objectives providing a base to promote, finance and extensively adopt innovative plant protection strategies within the Skåne region.